2009
DOI: 10.1177/1096348009344235
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Effect of Job Satisfaction and Empowerment On Customers’ Perception of Service Quality: a Study in the Restaurant Industry

Abstract: Empowerment, job satisfaction, and customer’s perception of service quality have been extensively researched in a multitude of industries. Although the service quality literature points out the importance of managing service quality from both customers’ and employees’ views, only a few studies have jointly considered an employee—customer research design. This study examined the answers from 474 restaurant contact employees and their 1,259 customers to determine the effects of empowerment and job satisfaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 58 publications
6
91
4
Order By: Relevance
“…These findings were consistent with previous empirical studies that showed that a significant relationship between structural empowerment and job satisfaction (e.g. Fulford and Enz, 1995;Dickson and Lorenz, 2009;Gazzoli et al, 2010;Pelit et al, 2011). This study also provides a support for the significant effect of psychological empowerment on employee job satisfaction (R 2 = 0.26, p<0.000).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings were consistent with previous empirical studies that showed that a significant relationship between structural empowerment and job satisfaction (e.g. Fulford and Enz, 1995;Dickson and Lorenz, 2009;Gazzoli et al, 2010;Pelit et al, 2011). This study also provides a support for the significant effect of psychological empowerment on employee job satisfaction (R 2 = 0.26, p<0.000).…”
Section: Discussionsupporting
confidence: 92%
“…Dickson and Lorenz (2009) confirmed that empowerment has a positive relationship with job satisfaction. Similar results were argued by Gazzoli et al (2010), they found that restaurant staff empowerment has a significant influence on job satisfaction. More recently, Pelit et al (2011) found that both behavioural empowerment and psychological empowerment have significant influence on job satisfaction in hotels, but the influence of whole empowerment is much greater when is combining both behavioural empowerment and psychological empowerment together.…”
Section: Empowerment and Job Satisfactionsupporting
confidence: 84%
See 3 more Smart Citations